PENGEMBANGAN MEDIA CD INTERAKTIF MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMP - Hevy Risqi Maharani; M Abdul Basir (Universitas Muria Kudus, 2017)
This research is a development that aims to develop mathematical learning media in the form of an interactive CD. Interactive CD is supporting learning to improve problem solving ability junior high school students. Development of interactive CD using 4D model was modified. Results of the expert validation assessment showed interactive CD on the very good category with an average score of 4.23 out of a maximum range 5. Test the practicality of interactive CD shown by the positive responses from teachers and students. Results showed that the effectiveness of interactive CD has effective in improving problem solving abilities. This was demonstrated by the average problem solving ability of students that used interactive CD has achieved mastery of individual and classical. In addition, the average problem solving ability of students to use interactive CD was better that not using interactive CD.